Nkx3.1 controls the DNA repair response in the mouse prostate. Issue 4 (10th December 2015) - Zhang, Hailan; Zheng, Tian; Chua, Chee Wai; Shen, Michael; Gelmann, Edward P.
Abstract : BACKGROUND: The human prostate tumor suppressor NKX3.1 mediates the DNA repair response and interacts with the androgen receptor to assure faithful completion of transcription thereby protecting against TMPRSS2‐ERG gene fusion. To determine directly the effect of Nkx3.1 in vivo we studied the DNA repair response in prostates of mice with targeted deletion of Nkx3.1 . METHODS: Using both drug‐induced DNA damage and γ‐irradiation, we assayed expression of γ‐histone 2AX at time points up to 24 hr after induction of DNA damage. RESULTS: We demonstrated that expression of Nkx3.1 influenced both the timing and magnitude of the DNA damage response in the prostate. CONCLUSIONS: Nkx3.1 affects the DNA damage response in the murine prostate and is haploinsufficient for this phenotype. Prostate 76:402–408, 2016 . © 2015 The Authors. The Prostate published by Wiley Periodicals, Inc.